EFEKTIVITAS SISTEM INTEGRASI TRANSPORTASI UMUM DI WILAYAH JABODETABEK - Kevin Bonfilio Hosea; Teguh Yuwono (Journal of Politic and Government Studies, 2026)
Rapid population growth in the Jabodetabek area has led to significant mobility barriers, prompting the government to pursue the integration of public transportation systems as a strategic solution. This study aims to assess the quality of such integration developments and to measure their relationship with the effectiveness of the public transportation system in the Jabodetabek region. The research employs a mixed-methods approach with an explanatory sequential design, involving public service users and representatives from the Directorate General of Multimodal Transport Integration of the Ministry of Transportation as key informants. The quality of integration is comprehensively analyzed based on the five dimensions of Chowdhury and Ceder's theory: network, temporal, physical, information, and fare integration. The results indicate that the overall quality of transport integration in Jabodetabek has reached a high category, which is proven to have a positive relationship with the effectiveness of the public transportation system. Although the achievements across these five dimensions are considered good, this study identifies opportunities for further development to optimize integration aspects and achieve more maximal outcomes in serving regional mobility.